The ongoing Canon debate - Schutte, Flip (HTS teologiese studies, 2004)
The aim of this review article is to participate in the current “canon debate” among biblical scholars. The collection of essays, The Canon Debate, edited by Lee Martin McDonald and James A Sanders and published in November 2002 serves as point of departure. The thirty-two essays in this volume provide a summary of the most recent research, and as such it provides the necessary background for meaningful participation in the current debate. “The Canon debate” by McDonald & Sanders is probably the most comprehensive collection of essays ever published on canon formation in Judaism and Christianity. This 662-page volume includes essays on both the First Testament and the Second Testament, as well as the apocrypha and pseudepigrapha. The essays provide translations of most of the ancient primary sources, as well as meaningful summaries of scholarly debates, in addition to providing a useful guide to the extensive scholarly literature on the subject. The article argues that once you have discovered the canon, you can experience it anywhere, not only in canonical texts.